Preventivni ukrepi za izboljšanje varnosti transfuzije in virtualni transfuzijski laboratorij - Rožman, Primož (Zdravniški vestnik, 2002)
Background. Even though blood transfusion is a relatively safe form of therapy, because of the eventual administrative errors in the transfusion chain between the blood donor and the recipient of blood, transfusion errors still occur. Therefore, it is imperative to ensure an utmost extent of safety and reliability of all transfusion related procedures. The safety of blood transfusion can be improved by preventive actions, i.e. implementation of the total quality management concept, haemovigilance and virtual transfusion laboratory. In the resulting system, the information web, robotics, computer sciences and communication technologies ensuresafe and reliable identificationof the patients, blood donors, corresponding test samples and blood products. Apart form this; the modern technologies enable the automationof laboratory testing, the integrity of laboratory results and enable an optimal use of blood. Conclusions. For an improved transfusion safety in Slovenia, adoption of corresponding prevention as well as haemovigilance is necessary. Identification errors can be prevented by implementation of the wrist bands systems with the code bars for the tagging of the patient and his biological samples, whereas the administrative errors in the blood bank and transfusion laboratory can be prevented by implementation of information systems and automation. We assume that the virtual transfusion laboratory will become an integral part of the new Slovenian transfusion web and will speed up, unify and simplify today's methods of ordering and administering blood products. (Abstract truncated at 2000 characters).
Keywords: Abo blood-group system; ABO sistem krvnih skupin; avtomatizacija; Blood donors; Blood grouping and crossmatching; Blood transfusion; Bolnik, identifikacijski sistemi; Computer communication networks; Krvna transfuzija; Krvne skupine in navzkrižno določanje; Krvodajalci; Kvaliteta, nadzor; Patient identification systems; preventiva; Quality control; Računalniške mreže; security; transfuzija; transfuziologija; varnost